Adaptation and Resilience in African American Mothers - Barbara Jackson PhD, RN, BSN; Ermalynn M. Kiehl PhD, ARNP, CNS (SAGE Publishing, 2017)
The purpose of this study was to examine factors influencing adaptation and resiliency of inner-city low-income, African American mothers. The number of studies that examine the lived experience of African American mothers in low-income inner-city settings is limited. The factors explored in this study, which determine the family's ability to adapt to their life situation, include vulnerability, adaptation, and resiliency. Survey data and narrative inquiry were used to determine maternal adaptation and resilience. Quantitative data were gathered using a demographic inventory, a Family Adaptation, Partnership, Growth, Affection, and Resolve; Family Adaptation Inventory; and Family Dynamics Questionnaire. Qualitative data were gathered as the mother described her life history and answered semistructured interview questions. The mothers, who participated in this study, were clear about the principles and morals in which they believed and spent much of their time teaching those principles to their children. They believed that these rules would protect their children and ensure that their children would make good decisions in the future and help them reach their goals. They feared that their living situation could prevent their children from reaching their full potential in life. Preventing current risk situations and protecting their children from future harm was an urgent concern. This study provides evidence for resiliency in inner-city low-income African American mothers.